An exploratory investigation of e-business constraints among large organizations in Portugal - Morais, Elisabete Paulo (2010)
It is well recognized that e-business supports all parts of an organization’s value chain, and offer valuable competitive advantages to firms. It is imperative for an organization to identify potential constraints to ebusiness in order to minimize the risk derived from its e-business initiative. Hence, in this paper, we explore a range of constraints that the literature suggests influences e-business evolution, so that organizations could be better equipped in anticipating any difficulties while in progress through their e-business initiatives. Thirteen hypotheses were formulated and tested. Questionnaires were applied to investigate the research problem. It was administered to 1000 managing directors of the biggest (according to the amount of business) Portuguese enterprises. Results suggest that organizational constraints are more critical, such as, conflict with traditional trading partners, conflict with traditional business and e-business initiatives, reengineering business processes and resistance to change, among other.